The horizontal gene transfer of Agrobacterium T-DNAs into the series Batatas (Genus Ipomoea) genome is not confined to hexaploid sweetpotato - Quispe-Huamanquispe, D.G.; Gheysen, G.; Yang, Y.; Jarret, Robert L.; Rossel, G.; Kreuze, Jan F. (Springer, 2019)
The discovery of the insertion of IbT-DNA1 and IbT-DNA2 into the cultivated (hexaploid) sweetpotato [Ipomoea batatas (L.) Lam.] genome constitutes a clear example of an ancient event of Horizontal Gene Transfer (HGT). However, it remains unknown whether the acquisition of both IbT-DNAs by the cultivated sweetpotato occurred before or after its speciation. Therefore, this study aims to evaluate the presence of IbT-DNAs in the genomes of sweetpotato’s wild relatives belonging to the taxonomic group series Batatas. Both IbT-DNA1 and IbT-DNA2 were found in tetraploid I. batatas (L.) Lam. and had highly similar sequences and at the same locus to those found in the cultivated sweetpotato. Moreover, IbT-DNA1 was also found in I. cordatotriloba and I. tenuissima while IbT-DNA2 was detected in I. trifda. This demonstrates that genome integrated IbT-DNAs are not restricted to the cultivated sweetpotato but are also present in tetraploid I. batatas and other related species.